Analisis Rasio Likuiditas, Solvabilitas dan Profitabilitas untuk Mengukur Kinerja Keuangan pada PT Pertamina EP Jakarta Selatan Tahun 2019 - 2021 - Gunawan Aji; Evi Yuswijayanti; Rakha Mita Artanti; Kholis Zahrotin; Zaidan Zulfa A (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this research is to find out the financial performance of PT Pertamina EP South Jakarta as seen from the ratio of liquidity, solvency and profitability in 2019-2021. PT Pertamina EP is the main business sector of oil and gas. As for data collection techniques used documentation techniques. From the research that has been carried out, the results show that the liquidity ratio measured using the Current Ratio has decreased every year, from 2019 which was very good to 2021 which was not good. The solvency ratio is measured using the Debt to asset ratio and the Debt to equity ratio. The results of the Debt to asset ratio for 2019-2021 are said to be not good, while the results of the debt to equity ratio have decreased every year, which is shown in 2019 which is categorized as good, 2020 is quite good, and 2021 is not good. While the profitability ratio is measured using Net Profit Margin, which shows fluctuation results because in 2019 it was very good, but in 2020 it has decreased to be quite good, then in 2021 it has increased with very good criteria.